Pengaruh Komunikasi, Lingkungan Kerja, Dan Kedisiplinan Terhadap Kinerja Karyawan (Studi kasus UMKM Arumanis Haji Ardi Berbah) - Rahmawati, Novia Anggita (Universitas Muhammadiyah Metro, 2021)
This study aims to test whether communication, work environment, and discipline have a positive and significant effect on employee performance, as well as to test whether communication, work environment, and discipline variables can improve employee performance. With sampling using a non-probability sampling method using random incidental techniques from employees who work at UMKM Arumanis Haji Ardi. The population in this study amounted to 80 employees. The sample was calculated using the Slovin formula to get the result of 60 as a sample. The results of the communication variable t-count 1.418 have a significant effect, the work environment variable t-count 2.121 has a significant effect and the discipline variable t-count is 2.850 has a significant effect. So it can be concluded that of the three independent variables the results of the f test (simultaneous) show that the variables of communication, work environment, and discipline together have an effect on the performance of employees of UMKM Arumanis Haji Ardi. Keywords: Communication, Work Environment, Discipline, Employee Performance